Control and mechanical design of a multi-diameter tri-legged in- pipe traversing robot - Bandala, Argel A. (Animo Repository, 2019)
In this paper a versatile and adaptive in-pipe robot is designed and tested The existing problem of versatility and adaptability of in pipe inspection robots are addressed in this study. The robot is equipped with a screw type assembly, which uniformly contracts and retracts a tri-arm assembly of wheels connected to it. This mechanism ensures that the robot grips the pipe walls when the arms are expanded. The dynamic model of the robot is derived and implemented in a proportional integral controller. The robot can maintain vertical position by maintaining the force exerted on the screw system Simulations and experiments were conducted to determine the robustness and stability of the robot system In addition, the robot is also capable of rust mapping, which enables easier pipe monitoring. The rust mapping yielded an S3.2% success rate. © 2019 IEEE.